A high-entropy doped p2-type layered oxide positive electrode material and a preparation method thereof

CN122950432APending Publication Date: 2026-10-20SHANDONG UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611094910.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0003]但P2型层状氧化物自身存在明显的本征性能缺陷,充放电过程中有序Na+/空位排列及P2-O2相变会导致多个电压平台,且钠离子深度脱出时层状结构稳定性下降,可逆容量降低,最终造成倍率性能较差、长循环容量衰减较快

Benefits of technology

本发明提供了一种高熵掺杂P2型层状氧化物正极材料,通过特定化学式Na0.67Ni0.3-xMn0.7-yMzO2构建多元高熵掺杂体系,从原子尺度改善P2型层状氧化物本征缺陷。多种掺杂元素在晶格中产生协同效应:一方面通过调控电子结构提升材料本征电子电导率,同时扩大钠离子扩散通道,加快钠离子扩散速率;另一方面有效抑制充放电过程中有序Na+/空位排列及高压下的P2-O2相变,大幅降低体积变化率,缓解钠离子深度脱出时的层状结构坍塌问题,显著提升了可逆容量、循环稳定性及倍率性能。同时,该材料依托镍、锰等常见金属,可灵活调整掺杂元素组合,从源头规避昂贵稀缺的钴元素,降低原材料成本并保障供应链稳定。此外,该高熵掺杂体系特别适配焦耳热快速烧结工艺,利用毫秒级升降温特性,避免传统高温固相法中元素分布不均、晶格缺陷及化学计量比偏移等问题,简化工艺流程、提升产物形貌与性能的可控性及重现性,为规模化量产适配高压实电极结构的高性能正极材料提供了可靠支撑。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses a high-entropy doped P2-type layered oxide cathode material and its preparation method, belonging to the technical field of sodium-ion battery cathode materials. The chemical formula is Na. 0.67 Ni 0.3‑x Mn 0.7‑y M z O2 (0≤x≤0.2, 0<y≤0.06, 0<z≤0.05, M is at least three of Li, Co, Ca, Mg, Al, Cu, Zn, Mo, V, Cr, La, and Ce). By constructing a high-entropy system, a synergistic effect is generated at the atomic scale, optimizing the electronic structure to improve intrinsic conductivity, suppressing the P2-O2 phase transition and structural collapse under high pressure, reducing the volume change rate, and improving reversible specific capacity, cycle stability, and rate performance. It is adapted to Joule heating rapid sintering processes, utilizing millisecond-level heating and cooling characteristics to avoid elemental segregation and lattice defects in high-temperature solid-state methods, achieving controllable and reproducible product morphology and performance, simplifying the process, and supporting large-scale mass production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of sodium-ion battery cathode materials, specifically relating to a high-entropy doped P2-type layered oxide cathode material and its preparation method. Background Technology

[0002] Given the abundance and low cost of sodium resources, sodium-ion batteries have become a research hotspot in the field of large-scale energy storage due to their resource advantages. The development of high-performance cathode materials is key to improving their energy density and operating voltage. Among these, transition metal layered oxides (Na₂O₃) are crucial. x TMO2 (TM transition metal, selected from Ti, Mn, Fe, Co, Ni, Cu, etc.) has shown great potential for practical application due to its simple synthesis method, excellent electrochemical performance, and ease of industrialization. It has become one of the mainstream research directions for cathode materials of sodium-ion batteries and has attracted much attention from the industry.

[0003] However, P2-type layered oxides have obvious intrinsic performance defects, and ordered Na+ during charging and discharging... + Vacancy arrangement and the P2-O2 phase transition lead to multiple voltage plateaus, and the layered structure stability decreases with deep sodium ion extraction, resulting in reduced reversible capacity and ultimately poor rate performance and rapid capacity decay over long cycles. Simultaneously, existing mainstream high-temperature solid-state sintering processes have inherent shortcomings. Raw materials rely solely on high-temperature solid-state ion diffusion mixing, which lacks uniformity and easily leads to uneven elemental distribution and lattice defects. Furthermore, the difficulty in precisely matching sintering temperature and holding time causes a shift in the material's stoichiometry, further reducing discharge specific capacity and cycle stability. These two factors combined make it difficult for existing P2-type layered oxide cathode materials to achieve stable long-term cycle performance, failing to meet practical application requirements. Summary of the Invention

[0004] To address the shortcomings of existing technologies, the present invention aims to provide a high-entropy doped P2-type layered oxide cathode material and its preparation method.

[0005] To achieve the above objectives, the technical solution of the present invention is as follows: In a first aspect, the present invention provides a high-entropy-doped P2-type layered oxide cathode material, the chemical formula of which is Na. 0.67 Ni 0.3-x Mn 0.7-y M z O2, where 0≤x≤0.2, 0<y≤0.06, 0<z≤0.05, and M is at least three of Li, Co, Ca, Mg, Al, Cu, Zn, Mo, V, Cr, La and Ce.

[0006] A second aspect of the present invention provides a method for preparing the high-entropy doped P2-type layered oxide cathode material described in the first aspect, comprising: Manganese source compound, nickel source compound, and dopant compound were mixed with water according to the specified ratio to obtain solution 1; urea was added to solution 1 to obtain solution 2. Solution 2 was subjected to a hydrothermal reaction to obtain a coprecipitate; The coprecipitate and sodium source compound were mixed according to the specified ratio to obtain the precursor powder; The precursor powder was sintered at a heating rate of 500℃ / 100 ms-1000℃ / ms and a heating time of 100-1000ms. The holding temperature was 800-1200℃ and the holding time was 50-300 s. After the holding time was completed, the material was naturally cooled to room temperature to obtain a high-entropy doped P2-type layered oxide cathode material.

[0007] A third aspect of the present invention provides an application of the high-entropy-doped P2-type layered oxide cathode material described in the first aspect in a sodium-ion battery.

[0008] According to four aspects of the present invention, a sodium-ion battery is provided, comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises the high-entropy-doped P2-type layered oxide positive electrode material described in the first aspect.

[0009] The beneficial effects of this invention are as follows: This invention provides a high-entropy doped P2-type layered oxide cathode material, achieved through the specific chemical formula Na... 0.67 Ni 0.3-x Mn 0.7-y M z O2 is used to construct a multi-element high-entropy doping system, improving the intrinsic defects of P2-type layered oxides at the atomic scale. Multiple dopants produce a synergistic effect in the crystal lattice: on the one hand, they enhance the intrinsic electronic conductivity of the material by regulating the electronic structure, while simultaneously expanding the sodium ion diffusion channels and accelerating the sodium ion diffusion rate; on the other hand, they effectively suppress the ordered Na+ diffusion during charging and discharging. + The vacancy arrangement and P2-O2 phase transition under high pressure significantly reduce the volume change rate, alleviating the layered structure collapse problem during deep sodium ion extraction, and significantly improving reversible capacity, cycle stability, and rate performance. Simultaneously, relying on common metals such as nickel and manganese, the combination of doping elements can be flexibly adjusted, avoiding expensive and scarce cobalt elements from the source, reducing raw material costs and ensuring supply chain stability. Furthermore, this high-entropy doping system is particularly suitable for Joule heating rapid sintering processes, utilizing millisecond-level heating and cooling characteristics to avoid problems such as uneven element distribution, lattice defects, and stoichiometric deviations in traditional high-temperature solid-state methods. This simplifies the process flow, improves the controllability and reproducibility of product morphology and performance, and provides reliable support for the large-scale mass production of high-performance cathode materials adapted to high-pressure solid electrode structures. Attached Figure Description

[0010] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.

[0011] Figure 1 The image shows an electron microscope (EM) image of the spherical Ni, Mn and doped ion precipitates obtained in step three of Example 1 of this invention.

[0012] Figure 2 This is an electron microscope image of the high-entropy doped P2-type layered oxide cathode material obtained in Example 1 of the present invention.

[0013] Figure 3 The curve shows the capacity decay of a coin cell assembled from the high-entropy-doped P2-type layered oxide cathode material obtained in Example 1 of this invention after 300 cycles at 1C rate.

[0014] Figure 4 The capacity change curve of a coin cell assembled with the high-entropy doped P2-type layered oxide cathode material obtained in Example 1 of this invention after 40 cycles at a rate of 0.1C-10C.

[0015] Figure 5 The first charge-discharge curve of the coin cell assembled with the high-entropy doped P2-type layered oxide cathode material obtained in Example 1 of this invention is shown at a 0.1C rate.

[0016] Figure 6 The image shows the XRD pattern of the high-entropy doped P2-type layered oxide cathode material obtained in Example 1 of this invention. Detailed Implementation

[0017] Given the shortcomings of existing P2-type layered oxide cathode materials in terms of intrinsic electrochemical performance (especially capacity decay caused by phase transition under high voltage), high resource costs (dependence on cobalt), and the difficulty of meeting the core pain points of large-scale production of high-performance materials by traditional high-temperature solid-state preparation processes, this invention proposes a high-entropy doped P2-type layered oxide cathode material.

[0018] A first typical embodiment of the present invention provides a high-entropy doped P2-type layered oxide cathode material with the chemical formula Na. 0.67 Ni 0.3-x Mn 0.7-y M z O2, where 0≤x≤0.2, 0<y≤0.06, 0<z≤0.05, and M is at least three of Li, Co, Ca, Mg, Al, Cu, Zn, Mo, V, Cr, La and Ce.

[0019] This invention utilizes the high-entropy effect to construct a multi-element doping system at the atomic scale. By introducing at least three doping elements, a strong synergistic effect is generated within the crystal lattice. On the one hand, this optimizes the electronic structure to improve intrinsic conductivity and broaden ion channels; on the other hand, it utilizes multi-element interactions to suppress high voltage (4.5 V vs. Na). + This invention addresses the harmful phase transition and structural collapse of the NaP2-O2 phase, fundamentally resolving the inherent defects of traditional materials such as large volume changes and poor cycle stability. Simultaneously, this system eliminates the need for expensive cobalt, ensuring low-cost and stable supply of raw materials. Furthermore, for this high-entropy system, this invention innovatively introduces a Joule heating rapid sintering process. This process overcomes the bottlenecks of uneven mixing and difficult parameter control in traditional high-temperature solid-state methods, utilizing millisecond-level rapid heating and cooling characteristics to effectively suppress abnormal grain growth and elemental segregation, achieving precise control over product morphology and performance. This synergistic effect of high-entropy design and rapid sintering provides a sodium-ion battery cathode material solution for large-scale energy storage applications, offering advantages such as excellent high-voltage cycle life, high safety, and low cost.

[0020] In this invention, when M is Li, La, or Ce, the chemical formula of the high-entropy doped P2-type layered oxide cathode material is Na. 0.67 Ni 0.15 Mn 0.66 Li 0.15 La 0.02 Ce 0.02 O2. Li occupies sodium sites, while La and Ce occupy transition metal sites, forming a synergistic doping.

[0021] A high-entropy doping system constructed using M as Li, La, and Ce exhibits a significant synergistic effect among these three elements. This improves the structural instability of traditional P2 materials under high-pressure deep sodium deintercalation at the atomic level, achieving a simultaneous increase in reversible specific capacity and cycle stability. Specifically, Li occupies sodium sites, effectively modulating the covalent nature of the TM-O bond, optimizing the electronic structure, and significantly improving the intrinsic electronic conductivity of the material. Simultaneously, the introduction of Li helps stabilize the sodium layer structure and broadens the sodium ion diffusion channels. La / Ce, with its larger ionic radius, broadens the sodium ion channels and acts as a structural pillar, effectively increasing the interlayer spacing, reducing the migration barrier during sodium ion insertion / extraction, effectively suppressing the harmful P2-O2 phase transition and layered structure collapse under high pressure, and significantly reducing the volume change rate during charge and discharge.

[0022] In this invention, when M is Li, Mg, or Al, the chemical formula of the high-entropy doped P2-type layered oxide cathode material is Na. 0.67 Ni 0.15 Mn 0.66 Li 0.15 Mg 0.02 Al0.02 O2. Li occupies sodium sites, while Mg and Al occupy transition metal sites.

[0023] Na constructed with M as Li, Mg and Al 0.67 Ni 0.15 Mn 0.66 Li 0.15 Mg 0.02 Al 0.02 O2 further verifies that the synergistic concept of high-entropy doping + Joule heating rapid sintering of this invention has universality in doped systems (Li, Co, Ca, Mg, Al, Cu, Zn, Mo, V, Cr, La, and Ce). At the atomic scale, Li, Mg, and Al produce a multidimensional synergistic effect; Li optimizes the electronic structure and improves intrinsic conductivity, while Mg... 2+ By leveraging its moderate ionic radius to broaden sodium ion channels and act as an interlayer support, it increases c-axis interlayer spacing and reduces Na+ ion concentration. + The high migration barrier and high Mg-O bond energy enhance the layered framework under high pressure; Al 3+ With a small radius and strong Al-O bond energy, these components significantly enhance lattice rigidity upon entering the TM site, suppressing Jahn-Teller distortion and layer collapse during high-pressure deep sodium removal. These three factors respectively inhibit harmful P2-O2 phase transitions and structural collapse under high pressure from three dimensions: electron transport, ion migration, and structural stability, fundamentally improving the high-pressure capacity decay problem of traditional materials.

[0024] A second typical embodiment of the present invention provides a method for preparing the high-entropy doped P2-type layered oxide cathode material, comprising: Manganese source compound, nickel source compound, and dopant compound were mixed with water according to the specified ratio to obtain solution 1; urea was added to solution 1 to obtain solution 2. Solution 2 was subjected to a hydrothermal reaction to obtain a coprecipitate; The coprecipitate and sodium source compound were mixed according to the specified ratio to obtain the precursor powder; The precursor powder was sintered at a heating rate of 500℃ / 100 ms-1000℃ / ms and a heating time of 100-1000ms. The holding temperature was 800-1200℃ and the holding time was 50-300 s. After the holding time was completed, the material was naturally cooled to room temperature to obtain a high-entropy doped P2-type layered oxide cathode material.

[0025] To address the elemental segregation and lattice defects caused by uneven mechanical mixing in traditional high-temperature solid-state methods, this invention employs urea-assisted hydrothermal co-precipitation, utilizing the slow release of OH- from urea. - / CO3 2-The characteristics of this material enable Ni, Mn, and multi-element dopants to nucleate simultaneously at the atomic scale, obtaining a precursor with uniform composition and eliminating microscopic inhomogeneities at the source. Secondly, addressing the stoichiometric deviation and structural degradation caused by the difficulty in matching sintering temperature / time in traditional processes, this invention introduces Joule thermal rapid sintering technology. The millisecond-level rapid heating and cooling effectively suppresses abnormal grain growth and element diffusion segregation, completing crystallization in a very short time while retaining the stabilizing effect of high-entropy doping. This improves the problem of structural collapse and capacity decay caused by the P2-O2 phase transition in P2-type materials under high pressure, realizing the preparation of cathode materials with high specific capacity, excellent long-cycle stability, and potential for large-scale mass production.

[0026] In this invention, urea acts as a homogeneous precipitant, remaining stable at room temperature and in aqueous solution without causing sudden pH changes in the system. When the temperature is raised above 90°C, urea undergoes slow hydrolysis to generate NH3 and CO2, with NH3 further dissociating to release OH-. - CO2 is converted to CO3 under alkaline conditions. 2- It provides OH uniformly and slowly in the system. - With CO3 2- A dual precipitation source allows for the simultaneous co-precipitation of nickel ions, manganese ions, and doped metal ions, resulting in a homogeneous co-precipitate precursor. Simultaneously, the NH3 produced during urea decomposition and the trace reducing atmosphere inhibit the precipitation of Mn. 2+ Oxidation and Ce 3+ Valence state drift ensures the stoichiometric accuracy of the high-entropy doped system. The addition of excess urea ensures complete precipitation and avoids localized over-alkaliness.

[0027] In this invention, the total concentration of manganese, nickel and dopant ions in solution 1 is 0.17 mol / L.

[0028] In this invention, the pH of solution 2 is 5.

[0029] In this invention, the manganese source compound is selected from any one or more of manganese bromide, manganese iodide, manganese fluoride, manganese nitrate, and manganese sulfate.

[0030] In this invention, the nickel source compound is selected from any one or more of nickel sulfate, nickel fluoride, nickel chloride, and nickel acetate.

[0031] In this invention, the sodium source compound is selected from any one or more of sodium carbonate, sodium bicarbonate, sodium nitrate, sodium acetate, sodium oxalate, and sodium hydroxide.

[0032] In this invention, the hydrothermal reaction is carried out at a temperature of 150-250°C for a time of 24-48 hours.

[0033] Within the temperature range of 150-250℃, urea can stably and fully hydrolyze to generate a precipitant, promoting the simultaneous co-precipitation of Ni, Mn, and multi-element dopants at the molecular scale. This results in a highly crystalline and uniformly composed co-precipitate, eliminating elemental segregation and lattice defects caused by local concentration differences. Simultaneously, a suitable reaction time of 24-48 hours ensures sufficient growth and uniform morphology of the precursor particles, laying the foundation for the subsequent high-voltage solid electrode structure. If this parameter is out of control, for example, a temperature below 150℃ will lead to an excessively slow reaction rate and incomplete precipitation, while a temperature above 250℃ will cause violent decomposition of urea, resulting in localized over-alkaliness and component segregation. A time less than 24 hours cannot guarantee crystal integrity, while a time exceeding 48 hours can easily lead to abnormal particle growth or agglomeration, both of which directly cause the precursor uniformity to fail. Consequently, even rapid Joule heating cannot compensate for the initial microstructural defects, ultimately failing to suppress the P2-O2 phase transition and capacity decay under high pressure.

[0034] In this invention, sintering can be performed using a rapid heating device, specifically a Joule ultrafast heating device. The Joule ultrafast heating device ensures rapid heating.

[0035] In this invention, the sintering carrier platform is any one of graphite paper, graphite boat, graphite sheet, and graphite tube; the sintering atmosphere is any one of air, argon, oxygen, and nitrogen. Graphite carriers have excellent electrical and thermal conductivity, which naturally matches the instantaneous high-current heating mode of Joule heating, ensuring a rapid heating curve of 500℃ / 100 ms to 1000℃ / ms. This allows the precursor to cross the low-temperature diffusion region and directly enter the high-temperature crystallization region within milliseconds, suppressing the long-range diffusion segregation of Ni, Mn, and multi-element dopants. The four atmospheres of air, argon, oxygen, and nitrogen cover the sintering requirements of the P2 system from inert protection (argon / nitrogen) to moderate oxidation (air / oxygen), and none of them introduce corrosive impurities such as sulfur and halogens, thus not disrupting the regularity of the high-entropy lattice.

[0036] If insulating / low thermal conductivity crucibles such as alumina and corundum are used, the Joule heating current cannot be effectively applied or the thermal response is sluggish, the advantage of rapid heating is lost, and the process reverts to the old path of element segregation in traditional slow sintering. If a strong reducing atmosphere such as pure H2 is used, the metal ions are excessively reduced, which disrupts the electrochemical stoichiometry of the P2 phase and may even induce impurities, causing the suppression of the P2-O2 phase transition under high pressure to fail and the cycle decay to intensify.

[0037] In this invention, when M is Li, La, or Ce, the preparation method includes: Manganese source compound, nickel source compound, lanthanum source compound and cerium source compound were mixed with water according to the ratio to obtain solution 1; urea was added to solution 1 to obtain solution 2; Solution 2 was subjected to a hydrothermal reaction to obtain a coprecipitate; The co-precipitate, sodium source compound, and lithium source compound were mixed according to the specified ratio, and a dispersant was added and the mixture was ground to obtain the precursor powder. The precursor powder was sintered to obtain a high-entropy doped P2-type layered oxide cathode material.

[0038] The lanthanum source compound is selected from any one or more of lanthanum bromide, lanthanum fluoride, lanthanum nitrate, and lanthanum chloride; the cerium source compound is selected from any one or more of cerium formate, cerium acetate, cerium chloride, and cerium nitrate; and the lithium source compound is selected from any one or more of lithium carbonate, lithium hydroxide, lithium fluoride, lithium oxide, and lithium nitride.

[0039] The dispersant is selected from any one of methanol, acetone, and anhydrous ethanol. During the grinding and mixing process, the dispersant can rapidly wet the raw materials, breaking up agglomerates through the combined effects of mechanical force and solvent wetting, enabling the multi-component components to achieve uniform molecular-level mixing at the microscale. This provides a homogeneous precursor basis for subsequent Joule heating rapid sintering. Simultaneously, the dispersant is chemically stable and does not undergo complexation or redox reactions with metal ions, preventing the introduction of impurities that could disrupt the high-entropy crystal lattice.

[0040] In this invention, the amount of dispersant added is 1.5-2 mL / g, the grinding speed is 350-500 rpm, and the grinding time is 8-12 h. This parameter range ensures that the co-precipitate, sodium source compound, and lithium source compound are fully wetted and uniformly mixed at the microscale, while avoiding the introduction of impurities or excessive particle refinement due to excessively high rotation speed / time. It also avoids incomplete wetting due to insufficient dispersant and decreased grinding efficiency and precursor oxidation due to excessive dispersant.

[0041] In this invention, when M is Li, Mg, or Al, the preparation method includes: Manganese source compound, nickel source compound, aluminum source compound and magnesium source compound were mixed with water according to the ratio to obtain solution 1; urea was added to solution 1 to obtain solution 2; Solution 2 was subjected to a hydrothermal reaction to obtain a coprecipitate; The co-precipitate, sodium source compound, and lithium source compound were mixed according to the specified ratio, and a dispersant was added and the mixture was ground to obtain the precursor powder. The precursor powder was sintered to obtain a high-entropy doped P2-type layered oxide cathode material.

[0042] A third aspect of the present invention provides an application of the aforementioned high-entropy doped P2-type layered oxide cathode material in a sodium-ion battery.

[0043] A fourth aspect of the present invention provides a sodium-ion battery comprising a positive electrode, a negative electrode, and an electrolyte, wherein the positive electrode comprises the aforementioned high-entropy-doped P2-type layered oxide positive electrode material.

[0044] To address the problems of poor cycle stability, low coulombic efficiency, and susceptibility to high-pressure phase transitions in traditional P2-type layered oxide cathode materials, as well as the excessively long sintering time associated with conventional high-temperature solid-state methods, this invention provides a high-entropy-doped P2-type layered oxide cathode material. Through co-precipitation, hydrothermal methods, and Joule heating for rapid temperature rise, this material suppresses the formation of Na+. + This invention improves cycle stability by building upon materials with vacancy-ordered structures, suppressing the deterioration in cycle performance caused by undesirable P2-O2 phase transitions under high pressure. The preparation method is simple, and the prepared material exhibits good cycle performance, showing promising application prospects in sodium-ion battery cathode materials and contributing to the widespread adoption of sodium-ion batteries.

[0045] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments.

[0046] Unless otherwise specified, the raw materials used in the following embodiments are all commercially available analytical grade, and the equipment used is conventional chemical and battery preparation equipment; the sintering equipment is a Joule ultrafast heating equipment and an inert atmosphere tube furnace, and the electrode preparation and battery charge-discharge test are all conventional test methods in the field of sodium-ion batteries.

[0047] Example 1 This embodiment provides a high-entropy doped P2-type layered oxide cathode material with the chemical formula Na. 0.67 Ni 0.15 Mn 0.66 Li 0.15 La 0.02 Ce 0.02 O2. The specific preparation steps are as follows: Step 1: Using Na 0.67 Ni 0.15 Mn 0.66 Li 0.15 La 0.02 Ce 0.02 The stoichiometric ratio of O2 was determined by weighing nickel nitrate, manganese nitrate, lanthanum nitrate, and cerium nitrate. The raw materials were dissolved in deionized water. After complete dissolution, the sample was stirred with urea at a molar ratio of 1:1.5 until completely dissolved. The total concentration of Ni, Mn ions and doped M ions was 0.17 mol / L, and the pH of the solution was 5.

[0048] Step 2: Transfer the solution obtained in Step 1 to a stainless steel hydrothermal reactor lined with polytetrafluoroethylene, and keep it at 180°C for 24 hours in a vacuum drying oven to form a coprecipitate. After cooling, remove the solution and discard the supernatant.

[0049] Step 3: The coprecipitate obtained in Step 2 is washed repeatedly by centrifugation with deionized water and anhydrous ethanol to remove residual ions. Finally, the washed product is dried in a vacuum drying oven at 80℃ for 12 h to obtain spherical Ni, Mn and doped ion precipitates.

[0050] Step 4: Mix the spherical Ni, Mn and doped ion precipitates obtained in Step 3 with lithium carbonate and sodium carbonate in a molar ratio, add a dispersant (anhydrous ethanol), and grind and mix thoroughly to obtain precursor powder.

[0051] Step 5: Place the precursor powder obtained in Step 4 into a graphite boat carrier, load it into a Joule heating rapid heating device, introduce an oxygen atmosphere and maintain it for ten minutes, heat it to 950℃ at a heating rate of 500℃ / 100 ms, hold it at that temperature for 150 s, and after the holding time is completed, allow it to cool naturally to room temperature to obtain a high-entropy doped P2 type layered oxide cathode material.

[0052] Example 2 This embodiment provides a high-entropy doped P2-type layered oxide cathode material with the chemical formula Na. 0.67 Ni 0.15 Mn 0.66 Li 0.15 Mg 0.02 Al 0.02 O2. The specific preparation steps are as follows: Step 1: Using Na 0.67 Ni 0.15 Mn 0.66 Li 0.15 Mg 0.02 Al 0.02 The stoichiometric ratio of O2 was determined by weighing nickel nitrate, manganese nitrate, aluminum nitrate, and magnesium nitrate. The raw materials were dissolved in deionized water. After complete dissolution, the sample was mixed with urea at a molar ratio of 1:1.5 and stirred until completely dissolved. The total concentration of Ni, Mn ions and doped M ions was 0.17 mol / L, and the pH of the solution was 5.

[0053] Step 2: Transfer the solution obtained in Step 1 to a stainless steel hydrothermal reactor lined with polytetrafluoroethylene, and keep it at 180°C for 24 hours in a vacuum drying oven to form a coprecipitate. After cooling, remove the solution and discard the supernatant.

[0054] Step 3: The coprecipitate obtained in Step 2 is washed repeatedly by centrifugation with deionized water and anhydrous ethanol to remove residual ions. Finally, the washed product is dried in a vacuum drying oven at 80℃ for 12 h to obtain spherical Ni, Mn and doped ion precipitates.

[0055] Step 4: Mix the spherical Ni, Mn and doped ion precipitates obtained in Step 3 with lithium carbonate and sodium carbonate in a molar ratio, add a dispersant (anhydrous ethanol), and grind and mix thoroughly to obtain precursor powder.

[0056] Step 5: Place the precursor powder obtained in Step 4 into a graphite boat carrier, load it into a Joule heating rapid heating device, introduce an oxygen atmosphere and maintain it for ten minutes, heat it to 950℃ at a heating rate of 500℃ / 100 ms, hold it at that temperature for 150 s, and after the holding time is completed, allow it to cool naturally to room temperature to obtain a high-entropy doped P2 type layered oxide cathode material.

[0057] Example 3 This embodiment provides a high-entropy doped P2-type layered oxide cathode material with the chemical formula Na. 0.67 Ni 0.15 Mn 0.66 Li 0.15 Co 0.02 Cu 0.02 O2. The specific preparation steps are as follows: Step 1: Using Na 0.67 Ni 0.15 Mn 0.66 Li 0.15 Co 0.02 Cu 0.02 The stoichiometric ratio of O2 was determined by weighing nickel nitrate, manganese nitrate, cobalt nitrate, and copper nitrate. The above raw materials were dissolved in deionized water. After complete dissolution, the sample and urea were added at a molar ratio of 1:1.5 and stirred until completely dissolved. The total concentration of Ni, Mn ions and doped M ions was 0.17 mol / L, and the pH of the solution was 5.

[0058] Step 2: Transfer the solution obtained in Step 1 to a stainless steel hydrothermal reactor lined with polytetrafluoroethylene, and keep it at 180°C for 24 hours in a vacuum drying oven to form a coprecipitate. After cooling, remove the solution and discard the supernatant.

[0059] Step 3: The coprecipitate obtained in Step 2 is washed repeatedly by centrifugation with deionized water and anhydrous ethanol to remove residual ions. Finally, the washed product is dried in a vacuum drying oven at 80℃ for 12 h to obtain spherical Ni, Mn and doped ion precipitates.

[0060] Step 4: Mix the spherical Ni, Mn and doped ion precipitates obtained in Step 3 with lithium carbonate and sodium carbonate in a molar ratio, add a dispersant (anhydrous ethanol), and grind and mix thoroughly to obtain precursor powder.

[0061] Step 5: Place the precursor powder obtained in Step 4 into a graphite boat carrier, load it into a Joule heating rapid heating device, introduce an oxygen atmosphere and maintain it for ten minutes, heat it to 950℃ at a heating rate of 500℃ / 100 ms, hold it at that temperature for 150 s, and after the holding time is completed, allow it to cool naturally to room temperature to obtain a high-entropy doped P2 type layered oxide cathode material.

[0062] Example 4 This embodiment provides a high-entropy doped P2-type layered oxide cathode material with the chemical formula Na. 0.67 Ni 0.15 Mn 0.66 Li 0.15 Ca 0.02 Zn 0.02 O2. The specific preparation steps are as follows: Step 1: Using Na 0.67 Ni 0.15 Mn 0.66 Li 0.15 Ca 0.02 Zn 0.02 The stoichiometric ratio of O2 was determined by weighing nickel nitrate, manganese nitrate, calcium nitrate, and zinc nitrate. The raw materials were dissolved in deionized water. After complete dissolution, the sample was mixed with urea at a molar ratio of 1:1.5 and stirred until completely dissolved. The total concentration of Ni, Mn ions and doped M ions was 0.17 mol / L, and the pH of the solution was 5.

[0063] Step 2: Transfer the solution obtained in Step 1 to a stainless steel hydrothermal reactor lined with polytetrafluoroethylene, and keep it at 180°C for 24 hours in a vacuum drying oven to form a coprecipitate. After cooling, remove the solution and discard the supernatant.

[0064] Step 3: The coprecipitate obtained in Step 2 is washed repeatedly by centrifugation with deionized water and anhydrous ethanol to remove residual ions. Finally, the washed product is dried in a vacuum drying oven at 80℃ for 12 h to obtain spherical Ni, Mn and doped ion precipitates.

[0065] Step 4: Mix the spherical Ni, Mn and doped ion precipitates obtained in Step 3 with lithium carbonate and sodium carbonate in a molar ratio, add a dispersant (anhydrous ethanol), and grind and mix thoroughly to obtain precursor powder.

[0066] Step 5: Place the precursor powder obtained in Step 4 into a graphite boat carrier, load it into a Joule heating rapid heating device, introduce an oxygen atmosphere and maintain it for ten minutes, heat it to 950℃ at a heating rate of 500℃ / 100 ms, hold it at that temperature for 150 s, and after the holding time is completed, allow it to cool naturally to room temperature to obtain a high-entropy doped P2 type layered oxide cathode material.

[0067] Example 5 This embodiment provides a high-entropy doped P2-type layered oxide cathode material with the chemical formula Na. 0.67 Ni 0.15 Mn 0.66 Li 0.15 La 0.02 Ce 0.02 O2. The specific preparation steps are as follows: Steps one through four are the same as in Example 1.

[0068] Step 5: Place the precursor powder obtained in Step 4 into a graphite boat carrier, load it into a Joule heating rapid heating device, introduce an oxygen atmosphere and maintain it for ten minutes, heat it to 1200℃ at a heating rate of 1000℃ / ms, hold it at that temperature for 50 s, and after the holding time is completed, allow it to cool naturally to room temperature to obtain a high-entropy doped P2 type layered oxide cathode material.

[0069] Example 6 This embodiment provides a high-entropy doped P2-type layered oxide cathode material with the chemical formula Na. 0.67 Ni 0.15 Mn 0.66 Li 0.15 La 0.02 Ce 0.02 O2. The specific preparation steps are as follows: Steps one through four are the same as in Example 1.

[0070] Step 5: Place the precursor powder obtained in Step 4 into a graphite boat carrier, load it into a Joule heating rapid heating device, introduce an oxygen atmosphere and maintain it for ten minutes, heat it to 800℃ at a heating rate of 500℃ / 100 ms, hold it at that temperature for 300 s, and after the holding time is completed, allow it to cool naturally to room temperature to obtain a high-entropy doped P2 type layered oxide cathode material.

[0071] Comparative Example 1 This comparative example uses a high-temperature solid-state method to prepare a cathode material with the same stoichiometric ratio as in Example 1. The specific preparation steps are as follows: Steps one through four are the same as in Example 1.

[0072] Step 5: The precursor powder obtained in Step 4 is heated to 950°C at a heating rate of 5°C / min and held at this temperature for 10 hours. After calcination, it is cooled to room temperature in the furnace to obtain the high-entropy doped P2-type layered oxide cathode material prepared by the high-temperature solid-state method.

[0073] Comparative Example 2 This comparative example provides a single-element doped (Li single-doped) cathode material with the chemical formula Na. 0.85 Ni 0.15 Mn 0.7 Li 0.15The specific preparation steps for O2 are as follows: Step 1: Using Na 0.85 Ni 0.15 Mn 0.7 Li 0.15 The stoichiometric ratio of O2 was determined by weighing nickel nitrate and manganese nitrate. The raw materials were dissolved in deionized water. After complete dissolution, the sample was mixed with urea at a molar ratio of 1:1.5 and stirred until completely dissolved. The total concentration of Ni and Mn ions was 0.17 mol / L, and the pH of the solution was 5.

[0074] Steps two through five are the same as in Example 1.

[0075] Comparative Example 3 This comparative example provides a single-element doped (Li and La dual-doped) cathode material with the chemical formula Na. 0.83 Ni 0.15 Mn 0.7 Li 0.15 La 0.02 The specific preparation steps for O2 are as follows: Step 1: Using Na 0.83 Ni 0.15 Mn 0.7 Li 0.15 La 0.02 The stoichiometric ratio of O2 was determined by weighing nickel nitrate, manganese nitrate, and lanthanum nitrate. The raw materials were dissolved in deionized water. After complete dissolution, the sample was mixed with urea at a molar ratio of 1:1.5 and stirred until completely dissolved. The total concentration of Ni, Mn, and doped ions was 0.17 mol / L, and the pH of the solution was 5.

[0076] Steps two through five are the same as in Example 1.

[0077] Comparative Example 4 This comparative example uses a high-temperature solid-state method to prepare a cathode material with the same stoichiometric ratio as in Example 1. The specific preparation steps are as follows: Steps one through four are the same as in Example 1.

[0078] Step 5: The precursor powder obtained in Step 4 is heated to 950℃ at a heating rate of 5℃ / min and held at this temperature for 150 s. After calcination, it is cooled to room temperature in the furnace to obtain the high-entropy doped P2-type layered oxide cathode material prepared by high-temperature solid-state method.

[0079] Example 7 This embodiment provides the application of the cathode material prepared in the examples and comparative examples in sodium-ion batteries.

[0080] The positive electrode material, conductive carbon black, and PVDF binder prepared in the examples and comparative examples were mixed at a mass ratio of 8:1:1 to form an electrode slurry, which was uniformly coated onto an aluminum foil current collector. After drying and rolling, a positive electrode sheet was formed. A sodium metal sheet was used as the counter electrode, glass fiber as the separator, and a carbonate electrolyte (1.0 M NaClO4 dissolved in EC:PC = 1:1 (volume ratio), with 10% FEC added) and additives as the electrolyte. CR2032 coin cells were assembled in an argon-protected glove box. The charge / discharge test voltage window of the battery was 1.5-4.5 V, the test environment temperature was 25℃, and constant current charge / discharge tests were performed using a current density of 0.1-10 C (1 C = 150 mAh / g). The test results are as follows: Figure 1-6 As shown in Table 1.

[0081] Table 1 Performance of cathode materials

[0082] Figure 1 These are spherical precipitates formed by co-precipitation after hydrothermal treatment. For example... Figure 2 As shown, the cathode material exhibits a uniform distribution and a near-regular hexagonal morphology after rapid Joule heating sintering. The regular and uniform hexagonal distribution of the sample demonstrates that the surface state of the sample is stable after sintering, with few structural defects.

[0083] Figure 3 The capacity decay curve of a coin cell assembled with the cathode material prepared in Example 1 of the present invention after 300 cycles at 1C rate. Figure 4 The capacity change curve of a coin cell assembled with the cathode material prepared in Example 1 of the present invention after 40 cycles at a rate of 0.1 C-10 C. Figure 5 The first charge-discharge curve of the coin cell assembled with the positive electrode material prepared in Example 1 of the present invention under 0.1C rate cycling. Figure 6 The image shows the XRD pattern of the high-entropy doped layered oxide cathode material prepared in Example 1 of this invention.

[0084] Depend on Figures 3-6As shown in Table 1, the batteries assembled from the high-entropy P2-type doped layered oxide cathode materials prepared in Examples 1-6 of this invention exhibit a 0.1 C discharge specific capacity of 117.3-123.7 mAh / g, which is 2.4-2.9 mAh / g higher than that of Comparative Examples 1-4 (114.9-120.8 mAh / g); the first-cycle efficiency reaches 93.5-94.7%, both higher than the comparative examples; and the capacity retention rate after 300 cycles at 1 C reaches 87.2-90.9%, both higher than that of Comparative Examples 1-3 (78.6%-87.4%). These results fully demonstrate that this invention, through the synergistic effect of high-entropy doping design combined with Joule heating rapid sintering process, effectively suppresses the harmful P2-O2 phase transition and structural collapse under high pressure, and improves the efficiency of Na... + The reversibility of insertion / extraction and intrinsic conductivity successfully solved the industry problem of severe phase change capacity loss under high voltage in traditional P2 layered oxide cathode materials, achieving synergistic improvement in long-cycle stability and specific capacity, and significantly improving the volumetric energy density of sodium-ion batteries.

[0085] This invention introduces three or more doping elements to construct a high-entropy crystal system, thereby controlling the electronic structure of the material at the atomic level, significantly improving the intrinsic conductivity and sodium ion migration kinetics, and fundamentally improving electrochemical performance. The preparation process of this invention is simple and highly controllable, enabling uniform doping of multiple elements while precisely controlling the microstructure of the product. It exhibits excellent experimental repeatability and has the potential for large-scale production. The resulting cathode material combines high reversible specific capacity with excellent long-cycle stability, demonstrating outstanding overall electrochemical performance and broad prospects for commercial application.

[0086] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A high-entropy doped P2-type layered oxide cathode material, characterized in that, Its chemical formula is Na 0.67 Ni 0.3-x Mn 0.7- y M z O2, where 0≤x≤0.2, 0<y≤0.06, 0<z≤0.05, and M is at least three of Li, Co, Ca, Mg, Al, Cu, Zn, Mo, V, Cr, La and Ce.

2. The high-entropy doped P2-type layered oxide cathode material as described in claim 1, characterized in that, When M is Li, La, or Ce, the chemical formula of the high-entropy doped P2-type layered oxide cathode material is Na. 0.67 Ni 0.15 Mn 0.66 Li 0.15 La 0.02 Ce 0.0 2O2; When M is Li, Mg, or Al, the chemical formula of the high-entropy doped P2-type layered oxide cathode material is Na. 0.67 Ni 0.15 Mn 0.66 Li 0.15 Mg 0.02 Al 0.02 O2. When M is Li, Co, or Cu, the chemical formula of the high-entropy doped P2-type layered oxide cathode material is Na. 0.67 Ni 0.15 Mn 0.66 Li 0.15 Co 0.02 Cu 0.02 O2. When M is Li, Ca, and Zn, the chemical formula of the high-entropy doped P2-type layered oxide cathode material is Na. 0.67 Ni 0.15 Mn 0.66 Li 0.15 Ca 0.02 Zn 0.02 O2.

3. A method for preparing the high-entropy doped P2-type layered oxide cathode material according to claim 1 or 2, characterized in that, include: Manganese source compound, nickel source compound, and dopant element compound were mixed with water according to the specified ratio to obtain solution 1; Add urea to solution 1 to obtain solution 2; Solution 2 was subjected to a hydrothermal reaction to obtain a coprecipitate; The coprecipitate and sodium source compound were mixed according to the specified ratio to obtain the precursor powder; The precursor powder was sintered at a heating rate of 500℃ / 100 ms-1000℃ / ms and a heating time of 100-1000 ms. The holding temperature was 800-1200℃ and the holding time was 50-300 s. After the holding time was completed, the material was naturally cooled to room temperature to obtain a high-entropy doped P2-type layered oxide cathode material.

4. The preparation method according to claim 3, characterized in that, The total concentration of manganese, nickel, and dopant ions in solution 1 is 0.17 mol / L; Preferably, the pH of solution 2 is 5.

5. The preparation method according to claim 3, characterized in that, The manganese source compound is selected from any one or more of manganese bromide, manganese iodide, manganese fluoride, manganese nitrate, and manganese sulfate; Preferably, the nickel source compound is selected from any one or more of nickel sulfate, nickel fluoride, nickel chloride, and nickel acetate; Preferably, the sodium source compound is selected from any one or more of sodium carbonate, sodium bicarbonate, sodium nitrate, sodium acetate, sodium oxalate, and sodium hydroxide.

6. The preparation method according to claim 3, characterized in that, The hydrothermal reaction is carried out at a temperature of 150-250℃ for a time of 24-48 h.

7. The preparation method according to claim 3, characterized in that, The sintering carrier platform can be any one of graphite paper, graphite boat, graphite sheet, and graphite tube; the sintering atmosphere can be any one of air, argon, oxygen, and nitrogen.

8. The preparation method according to any one of claims 3-7, characterized in that, When M is Li, La, or Ce, the preparation method includes: Manganese source compound, nickel source compound, lanthanum source compound and cerium source compound were mixed with water in a certain ratio to obtain solution 1; urea was added to solution 1 to obtain solution 2; Solution 2 was subjected to a hydrothermal reaction to obtain a coprecipitate; The co-precipitate, sodium source compound, and lithium source compound were mixed according to the specified ratio, and a dispersant was added and the mixture was ground to obtain the precursor powder. The precursor powder was sintered to obtain a high-entropy doped P2-type layered oxide cathode material. Preferably, the lanthanum source compound is selected from any one or more of lanthanum bromide, lanthanum fluoride, lanthanum nitrate, and lanthanum chloride; the cerium source compound is selected from any one or more of cerium formate, cerium acetate, cerium chloride, and cerium nitrate; and the lithium source compound is selected from any one or more of lithium carbonate, lithium hydroxide, lithium fluoride, lithium oxide, and lithium nitride. Preferably, the dispersant is selected from any one of methanol, acetone, and anhydrous ethanol; When M is Li, Mg, or Al, the preparation method includes: Manganese source compound, nickel source compound, aluminum source compound and magnesium source compound were mixed with water according to the ratio to obtain solution 1; urea was added to solution 1 to obtain solution 2; Solution 2 was subjected to a hydrothermal reaction to obtain a coprecipitate; The co-precipitate, sodium source compound, and lithium source compound were mixed according to the specified ratio, and a dispersant was added and the mixture was ground to obtain the precursor powder. The precursor powder was sintered to obtain a high-entropy doped P2-type layered oxide cathode material. When M is Li, Co, or Cu, the preparation method includes: Manganese source compound, nickel source compound, cobalt source compound and copper source compound were mixed with water according to the ratio to obtain solution 1; urea was added to solution 1 to obtain solution 2; Solution 2 was subjected to a hydrothermal reaction to obtain a coprecipitate; The co-precipitate, sodium source compound, and lithium source compound were mixed according to the specified ratio, and a dispersant was added and the mixture was ground to obtain the precursor powder. The precursor powder was sintered to obtain a high-entropy doped P2-type layered oxide cathode material. When M is Li, Ca, or Zn, the preparation method includes: Manganese source compound, nickel source compound, calcium source compound and zinc source compound were mixed with water in the specified ratio to obtain solution 1; urea was added to solution 1 to obtain solution 2; Solution 2 was subjected to a hydrothermal reaction to obtain a coprecipitate; The co-precipitate, sodium source compound, and lithium source compound were mixed according to the specified ratio, and a dispersant was added and the mixture was ground to obtain the precursor powder. The precursor powder was sintered to obtain a high-entropy doped P2-type layered oxide cathode material.

9. The application of the high-entropy doped P2-type layered oxide cathode material according to any one of claims 1 or 2 in sodium-ion batteries.

10. A sodium-ion battery, comprising a positive electrode, a negative electrode, and an electrolyte, characterized in that, The cathode comprises the high-entropy doped P2-type layered oxide cathode material as described in any one of claims 1 or 2.